Factors Associated with Irritant Contact Dermatitis Among Seaweed Farmers In Seppong Village, North Belopa District, Luwu Regency, South Sulawesi - Damayati , Dwi Santy; Widiastuty , Lilis; Afriansyah, Ahmad (Media Publikasi Cendekia Indonesia, 2025)
Irritant Contact Dermatitis is an immunological local inflammatory response of the skin characterized by redness and swelling after exposure to irritants such as solvents, detergents, and sawdust. This study aims to determine the relationship between age, gender, length of contact, personal hygiene, and nutritional status with symptoms of irritant contact dermatitis in seaweed farmers, using quantitative methods and cross-sectional study design on 139 respondents who work as seaweed farmers in Seppong Village, North Belopa District, which were selected using random sampling techniques using questionnaires and then analyzed using chi-square. The findings revealed significant associations between symptoms of irritant contact dermatitis and the following variables: age (p-value = 0.005), gender (p-value = 0.003), duration of contact (p-value = 0.006), length of service (p-value = 0.003), and personal hygiene (p-value = 0.002). In contrast, nutritional status was found to be unrelated (p-value = 0.147). The conclusion of this research is that age, gender, length of contact, length of service, and personal hygiene have a strong influence on irritant contact dermatitis, so it is recommended that seaweed farmers pay attention to personal health by maintaining personal hygiene and also avoiding direct contact with irritants by using complete and standard PPE